Early carcinoma tongue: evaluation using ultrasonography and its comparison with final histopathological findings - Kshirsagar, Pankaj; Shetty, Varun Sudarshan; Mody, Pratham; Gawade, Harshad Namdev (International Surgery Journal, 2018)
Background: Squamous cell carcinoma of the tongue is a common malignancy associated with risk factors like excessive alcohol consumption, heavy tobacco smoking and human papilloma virus. Magnetic resonance imaging (MRI) scan is considered to be the gold standard in investigating these tumors. However, MRI equipment is expensive to buy and is not readily available in some centers. Computed tomography scan has also been used in imaging these patients, but this modality carries a radiation burden. Patient’s five-year survival is dependent on early diagnosis. It is, therefore, important to diagnose early and image accurately to ensure good outcomes. This study was focused on evaluating the role of Ultrasonography in assessing early tongue cancer and its comparison with postoperative histopathological findings. The objectives of this study are to evaluate the role of sonography in assessing early tongue cancer depth of invasion and compared it with postoperative histopathological findings. Methods: A prospective study was performed on 100 cases of early tongue cancer. sonography of the tongue was performed, BY 7.5 MHz - 12 MHz Probe. Ultrasonography findings compared with post-operative histopathological findings sensitivity and specificity calculated. Results: All patients underwent sonography of tongue with 7.5 MHz probe to know the depth of tumor and these findings were compared with depth demonstrated on final histopathological reports. Sensitivity and specificity of USG for depth of tumor were very high (HPR findings were taken as standard results). On USG, tumor thickness i.e. 2 mm, 2-4 mm and >4 mm were observed in 22, 55 and 23 patients. On HPR, tumor thickness i.e. 2 mm, 2-4 mm and >4 mm were observed in 20, 60 and 20 patients. Sensitivity and septicity both above 90%. Conclusions: Ultrasonography proved a reliable diagnostic tool with sensitivity and specificity more than 90%, for knowing the pre-operative depth of tumor but further larger randomized studies required to confirm the recommendations.